Pyrolysis characteristics and kinetics of biomass torrefied in various atmospheres. (1st June 2017) - Bach, Quang-Vu; Trinh, Trung Ngoc; Tran, Khanh-Quang; Thi, Ngoc Bao Dung
Highlights: Norway spruce is torrefied in different conditions relevant to oxy-fuel combustion. Pyrolysis characteristics and kinetics of torrefied spruce are investigated. Effects of non-oxidative gases are unpronounced. Effects of oxygen are significant. Torrefaction temperature have strong effects on the kinetic data. Abstract: This study aims at investigating into the pyrolysis characteristics and kinetics of torrefied Norway spruce obtained from our previous work on development of a biomass torrefaction process integrated with oxy-fuel combustion. Thermogravimetric analysis technique was employed to study the effects of different torrefaction conditions (including various torrefaction atmospheres and different temperatures) relevant to oxy-fuel combustion on the pyrolysis behavior of the torrefied biomass. Thereafter, a global kinetic model with an assumption of a three-pseudocomponent mechanism was used for kinetic modeling and evaluation. The results showed that torrefaction temperature and oxygen concentration in torrefaction gas have significant effects on the pyrolysis peak height and peak temperature of the torrefied biomass. In addition, more hemicellulose was removed during torrefaction in CO2, compared with torrefaction in N2 and CO2 /H2 O. Moreover, high oxygen concentration in torrefaction gas and high torrefaction temperature can completely remove hemicellulose. The kinetic evaluation revealed that non-oxidative torrefaction atmospheres do not influent the pyrolysis kinetics of three main biomass components, but only their contribution factors. However, the presence of oxygen in torrefaction gas and the torrefaction temperature have significant effects on the kinetic data.